2015
DOI: 10.1002/sm2.79
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Masculine and Feminine Gender Roles in Iranian Patients with Gender Identity Disorder

Abstract: IntroductionGender identity disorders (GID) are heterogeneous disorders that may be influenced by culture and social norms.AimThe aim of this study was to determine masculine and feminine gender roles in a group of Iranian patients with GID and compare these roles with two control groups.MethodsTwelve male‐to‐female (MF) and 27 female‐to‐male (FM) individuals with GID referred to Tehran Psychiatric Institute in Tehran, I. R. Iran were evaluated by self‐report inventories and were compared with two groups of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In three studies in Iran, researchers compared gender roles between cisgender and transgender participants ( Alavi et al., 2015 ; Khorashad et al., 2019 ; Roshan et al., 2019 ). For example, Alavi and colleagues reported that compared to cisgender male and female participants, transgender participants had the highest and lowest score on the Gender Masculine scale, respectively; transgender men had the lowest score on the Gender Feminine scale of all groups ( Alavi et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In three studies in Iran, researchers compared gender roles between cisgender and transgender participants ( Alavi et al., 2015 ; Khorashad et al., 2019 ; Roshan et al., 2019 ). For example, Alavi and colleagues reported that compared to cisgender male and female participants, transgender participants had the highest and lowest score on the Gender Masculine scale, respectively; transgender men had the lowest score on the Gender Feminine scale of all groups ( Alavi et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Laws have been passed that support sex reassignment in people with ambiguous sexual identification in Iran, but they are subject to a great deal of mental pressure due to cultural norms (14). There are no accurate statistics which sexual and also high-risk behaviors such as drug abuse in transsexual persons in Iran.…”
Section: Introductionmentioning
confidence: 99%